2001
DOI: 10.1021/jf010258o
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Lipid Content in Potato Tubers Modified by 14-3-3 Gene Overexpression

Abstract: Recently, transgenic potato plants were created with overexpression of the 14-3-3 protein derived from Cucurbita pepo. Detailed analysis of those plants suggested that the function of the isolated 14-3-3 isoform is in the control of carbohydrate and lipid metabolism in the plants. 14-3-3 protein overexpression gave rise to an increase in soluble sugar and catecholamine contents in both leaves and tubers. It is proposed that 14-3-3 protein affects carbohydrate metabolism in potato plants via regulation of catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…The result of the fatty acid analysis of TL extracted from wild type D and GMP with overexpression of 14-3-3 protein J2 26 showed that the percentage of oleic, linoleic and linolenic acids is in great agreement with the published reports of Kolbe et al 32 and Trevini et al 33 . The content of linoleic acid, the main fatty acid of potato, was approximately 49 .…”
Section: Fatty Acid Compositionsupporting
confidence: 86%
See 2 more Smart Citations
“…The result of the fatty acid analysis of TL extracted from wild type D and GMP with overexpression of 14-3-3 protein J2 26 showed that the percentage of oleic, linoleic and linolenic acids is in great agreement with the published reports of Kolbe et al 32 and Trevini et al 33 . The content of linoleic acid, the main fatty acid of potato, was approximately 49 .…”
Section: Fatty Acid Compositionsupporting
confidence: 86%
“…Fatty acid profiling showed that linoleic acid was the main fatty acid of both GMP and non-genetically modified potato NGMP . In the non-polar fraction of lipids from GMP, the unsaturated fatty acids were found in higher levels 26,27 .…”
Section: Total Lipids and Lipid Classesmentioning
confidence: 95%
See 1 more Smart Citation
“…The direct evidence of role of 14-3-3 in lipid synthesis came from the genetically modiWed potato tubers with overexpressing 14-3-3 protein showed changes in lipid content and composition (Prescha et al 2001). However, the mechanism of this alteration is still unknown.…”
Section: Some Regulatory Proteinsmentioning
confidence: 99%
“…The potatoes also contained somewhat less crude fibre and more fat. A positive correlation between increased synthesis of 14-3-3 protein and a higher concentration of fat in potato tubers was also shown by Prescha et al (2001). It was also found that a significant increase in the nonpolar lipid fraction was associated with the overexpression of this protein.…”
Section: Resultsmentioning
confidence: 67%